1991
DOI: 10.1007/bf00053129
|View full text |Cite
|
Sign up to set email alerts
|

Smoking behavior following diagnosis in patients with Stage I non-small cell lung cancer

Abstract: The cigarette-smoking behavior of 840 patients with resected Stage I non-small cell lung cancer was analyzed prospectively for up to four years following diagnosis. Lung cancer patients were heavier smokers at diagnosis than other cancer patients and the general population. At one year, only 16.8 percent of the 317 current smokers at baseline, who were followed for two years or longer, continued to smoke, while 83.2 percent of patients either quit permanently (53.0 percent) or for some time period (30.2 percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
113
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 20 publications
6
113
2
3
Order By: Relevance
“…However, whereas estimates of quitting around the time of diagnosis are in the range of 35%-79% [49,50], about one third of nonadvanced-stage lung cancer patients resume smoking within the first year after surgery [50 -52]. Dr. Park and colleagues examined data from the Cancer Care Outcomes Research and Surveillance cohort survey and reported that 90% of lung cancer patients had a history of ever smoking and approximately one third of lung cancer patients reported smoking around the time of diagnosis [53].…”
Section: Lung Cancer Patients Who Continue To Smoke May Be Vulnerablementioning
confidence: 99%
See 3 more Smart Citations
“…However, whereas estimates of quitting around the time of diagnosis are in the range of 35%-79% [49,50], about one third of nonadvanced-stage lung cancer patients resume smoking within the first year after surgery [50 -52]. Dr. Park and colleagues examined data from the Cancer Care Outcomes Research and Surveillance cohort survey and reported that 90% of lung cancer patients had a history of ever smoking and approximately one third of lung cancer patients reported smoking around the time of diagnosis [53].…”
Section: Lung Cancer Patients Who Continue To Smoke May Be Vulnerablementioning
confidence: 99%
“…Dr. Park and colleagues examined data from the Cancer Care Outcomes Research and Surveillance cohort survey and reported that 90% of lung cancer patients had a history of ever smoking and approximately one third of lung cancer patients reported smoking around the time of diagnosis [53]. It is important to note that many participants reported quitting tobacco use prior to, during, and immediately following a cancer diagnosis, resulting in a significant group of lung cancer patients who were relatively new former smokers and thus vulnerable to smoking relapse [50].…”
Section: Lung Cancer Patients Who Continue To Smoke May Be Vulnerablementioning
confidence: 99%
See 2 more Smart Citations
“…5 For example, in a study of 317 smokers diagnosed with Mountain 6 Stage I nonsmall cell lung carcinoma (NSCLC), researchers found a 12-month tobacco abstinence rate of 53% and a 24-month tobacco abstinence rate of 47%. 7 Others have reported an 86% tobacco abstinence rate after thoracotomy for resection of a pulmonary malignancy. 8 Despite the importance of providing smoking cessation interventions for individuals either diagnosed with lung carcinoma or for those considered to be at high risk for developing lung carcinoma, this is an underinvestigated area.…”
mentioning
confidence: 99%